PENGARUH EFISIENSI DAN EFEKTIVITAS PAJAK HOTEL TERHADAPPENDAPATAN ASLI DAERAH KOTA BATAM - Jaya, Fernando Berrima; Nopiana, Puspita Rama (LPPM Universitas Putera Batam, 2019)
This research aims to determine the effect of efficiency and the effectiveness of hotel tax on the original revenue of Batam city in 2012-2017. The population in this research uses the sampling census method in the form of reports on the original revenue of Batam city for 5 years with 60 months of data. The test result shows that the efficiency of the hotel tax has a positive and partially significant effect on the local revenue. Meanwhile, the test result on the effectiveness of hotel tax has a positive and partially significant effect on the local revenue. Simultaneously, the efficiency and the effectiveness of hotel tax have a positive and significant influence on the local revenue.